Polarized transport of membrane and secreted proteins during lumen morphogenesis. (15th January 2023) - Levic, Daniel S.; Bagnat, Michel
Abstract: A ubiquitous feature of animal development is the formation of fluid-filled cavities or lumina, which transport gases and fluids across tissues and organs. Among different species, lumina vary drastically in size, scale, and complexity. However, all lumen formation processes share key morphogenetic principles that underly their development. Fundamentally, a lumen simply consists of epithelial cells that encapsulate a continuous internal space, and a common way of building a lumen is via opening and enlarging by filling it with fluid and/or macromolecules. Here, we discuss how polarized targeting of membrane and secreted proteins regulates lumen formation, mainly focusing on ion transporters in vertebrate model systems. We also discuss mechanistic differences observed among invertebrates and vertebrates and describe how the unique properties of the Na + /K + -ATPase and junctional proteins can promote polarization of immature epithelia to build lumina de novo in developing organs.